Satan's poetry: fallenness and poetic tradition in Paradise Lost - St. Hilaire, Danielle A. (Medieval & Renaissance literary studies, 2025)
"Readers of Paradise Lost have long been struck by two prominent aspects of the poem: its compelling depiction of Satan and its deep engagement with its literary tradition. Satan's Poetry brings these two issues together to respond to the resurgent interest in Milton's Satan by examining the origins of conflict and ambiguity in Paradise Lost"--